LOFAR MSSS: The scaling relation between AGN cavity power and radio luminosity at low radio frequencies - Kokotanekov, G.; Wise, M.; Heald, G.; McKean, J.; Bîrzan, L.; Rafferty, D.; Godfrey, L.; De Vries, M.; Intema, Hubertus; Broderick, J.; Hardcastle, M.; Bonafede, A.; et al. (EDP Sciences, 2017)
We present a new analysis of the widely used relation between cavity power and radio luminosity in clusters of galaxies with evidence for strong AGN feedback. We studied the correlation at low radio frequencies using two new surveys - the first alternative data release of the TIFR GMRT Sky Survey (TGSS ADR1) at 148 MHz and LOFAR's firstall-sky survey, the Multifrequency Snapshot Sky Survey (MSSS) at 140 MHz. We find a scaling relation Pcav Lß148Pcav L148ß, with a logarithmic slope of ß = 0.51 ± 0.14, which is in good agreement with previous results based on data at 327 MHz. The large scatter present in this correlation confirms the conclusion reached at higher frequencies that the total radio luminosity at a single frequency is a poor predictor of the total jet power. Previous studies have shown that the magnitude of this scatter can be reduced when bolometric radio luminosity corrected for spectral aging is used. We show that including additional measurements at 148 MHz alone is insufficient to improve this correction and further reduce the scatter in the correlation. For a subset of four well-resolved sources, we examined the detected extended structures at low frequencies and compare with the morphology known from higher frequency images and Chandra X-ray maps. In the case of Perseus we discuss details in the structures of the radio mini-halo, while in the 2A 0335+096 cluster we observe new diffuse emission associated with multiple X-ray cavities and likely originating from past activity. For A2199 and MS 0735.6+7421, we confirm that the observed low-frequency radio lobes are confined to the extents known from higher frequencies. This new low-frequency analysis highlights the fact that existing cavity power to radio luminosity relations are based on a relatively narrow range of AGN outburst ages. We discuss how the correlation could be extended using low frequency data from the LOFAR Two-metre Sky Survey (LoTSS) in combination with future, complementary deeper X-ray observations.